Tariff procedures and trade barriers a study of indirect protection in Canada and the United States. - Elliott, George A., 1901- (Heritage., 1955)
This book is intended as a source of information and enlightenment for that alert and critical public whose interest in international economic relations and constant awareness of facts have already provided a strong impetus to a world movement in favour of more liberal trade policies.